2022
DOI: 10.7554/elife.76554
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbial trimethylamine is elevated in alcohol-associated hepatitis and contributes to ethanol-induced liver injury in mice

Abstract: There is mounting evidence that microbes resident in the human intestine contribute to diverse alcohol-associated liver diseases (ALD) including the most deadly form known as alcohol-associated hepatitis (AH). However, mechanisms by which gut microbes synergize with excessive alcohol intake to promote liver injury are poorly understood. Furthermore, whether drugs that selectively target gut microbial metabolism can improve ALD has never been tested. We used liquid chromatography tandem mass spectrometry to qua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 82 publications
0
22
0
Order By: Relevance
“…gut microbiota are closely related to environmental influences such as sex, diet, and drugs administered during treatment (25).…”
Section: Changes In the Composition Of The Gut Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…gut microbiota are closely related to environmental influences such as sex, diet, and drugs administered during treatment (25).…”
Section: Changes In the Composition Of The Gut Microbiotamentioning
confidence: 99%
“…Indeed, the composition of the gut microbiota shows marked dynamic changes from birth to adulthood and old age ( 24 ). However, most alterations in the gut microbiota are closely related to environmental influences such as sex, diet, and drugs administered during treatment ( 25 ).…”
Section: Link Of Microbiota To the Non-alcoholic Fatty Liver Disease ...mentioning
confidence: 99%
“…DNA Extraction and 16S rRNA amplicon sequencing DNA Extraction and 16S sRNA amplicon sequencing were performed as described previously [16]. Briefly, DNA was isolated from stool samples using the QIAamp DNA Microbiome kit (Qiagen).…”
Section: Effect Of Antibiotic Treatment On the Intestinal Microbiotamentioning
confidence: 99%
“…Although accumulating evidence shows that ethanol is an important risk factor for osteoporosis, 5,6 it remains largely unknown how bone loss and osteopenia occur as parts of many unwanted consequences of ethanol consumption. It is recently reported that chronic heavy ethanol consumption directly impairs gut microbiota (GM) composition, which might be a pivotal pathogenic factor or aggravate pre‐existing illnesses 7 . Notably, studies have repeatedly shown that a gut‐bone regulatory axis exists, by which GM composition could indirectly regulate bone metabolism 8 .…”
Section: Introductionmentioning
confidence: 99%
“…It is recently reported that chronic heavy ethanol consumption directly impairs gut microbiota (GM) composition, which might be a pivotal pathogenic factor or aggravate pre‐existing illnesses. 7 Notably, studies have repeatedly shown that a gut‐bone regulatory axis exists, by which GM composition could indirectly regulate bone metabolism. 8 However, it remains largely unknown whether the osteoporosis caused by chronic heavy ethanol consumption is related to the impairments of GM composition.…”
Section: Introductionmentioning
confidence: 99%